Virtual Action Learning for Virtual Leadership Development. Issue 8 (8th October 2019) - Byrd, Lalaine
Abstract: Virtual organizations are challenged not only to develop the right skills for effective virtual leaders but to develop those skills among a geographically distributed workforce. This article explores a recent development in learning and development: virtual action learning (VAL). Specifically, this article discusses the compatibility of VAL with a dialogic/network application of path‐goal leadership theory and how the combination of these frameworks represents a potential learning‐design approach to effectively foster successful virtual leaders.